Edukasi Interaktif Berbasis Permainan untuk Meningkatkan Literasi Digital dan Pencegahan Cyber Bullying di Sekolah Dasar - Harahap, Heryani; Syarifah, Laila; Rianita, Resti; Jati, Putri Zulia (Journal of Social and Community Service, 2025)
The lack of elementary school students’ understanding of responsible information technology use poses a challenge in the digital era. This study aims to increase students’ awareness of cyber bullying through an interactive socialization program at SD Negeri 101630 Portibi. The activity was conducted over one hour with 30 fifth-grade students using educational games and a question-and-answer session. The approach was designed to suit the developmental characteristics of elementary school children. The results showed improved student understanding in recognizing the forms, impacts, and prevention of cyber bullying. Students also demonstrated more responsible behavior in using digital technology. The interactive method proved effective as a preventive effort against digital bullying. It is recommended that similar programs be implemented sustainably with the involvement of teachers and parents in supporting children's digital literacy.